The Significance of Vedic Science for Artificially Intelligent Systems - ., Anshuman; Kumar, Upendra (International Journal of Engineering and Technology, 2018)
The significance of Vedic Sciences is well proven. Vedic concepts are suitable as well as necessary for an efficient lead in the field of Artificial Intelligence (AI). The concept is very crisp: To lace the man-made machines with the ideology described in the Vedic scriptures, to build a better and smarter society. Well proven concepts to build better machines. Â Â